A Study on Work Life Balance among Women Employees in Public Sector Undertaking With Reference to Electronic Industries in Kerala - Anila K.P and V. Krishnaveni (International Journal of Advance Research in Computer Science and Management Studies, 2019)
Work life balance can be stated as a comfortable state of equilibrium achieved between an employee’s primary priorities of their employment position and their private life style. The pressure of an increasingly demanding work culture perhaps the biggest and most pressing challenge in the present scenario. The cumulative effect of increased working hours is having an important effect on the life style of a huge number of people, which is likely to prove damaging to their mental wellbeing. The study concludes that a moderate level of work life balance was found among the respondents. The study also found that demographic variables namely age, managerial level, educational qualification, experience, and number of dependents influence the level of work life balance.